The Application of a Multisensory Strategy Using Picture Word Cards to Improve Early Reading Skills in Elementary School Students - Ghina Fauziah; Mudopar Mudopar; Elin Rosmaya (Yayasan Pendidikan Bima Berilmu, 2026)
Early reading skills are fundamental abilities that elementary school students must develop, as they provide the foundation for successful learning at subsequent educational levels. However, many students still experience difficulties in recognizing letters and reading syllables, words, and simple sentences. This study aimed to describe the implementation of a multisensory strategy assisted by picture word cards and to examine its effect on elementary school students’ early reading skills. The study employed a quantitative approach using a quasi-experimental method with a One-Group Pretest–Posttest Design. The sample consisted of 11 first-grade students from SDN Pelandakan 1, selected through purposive sampling. Data were collected through tests and classroom observations and were analyzed using descriptive statistics, a normality test, a paired-sample t-test, and N-Gain analysis. The findings revealed that the implementation of a multisensory strategy assisted by picture word cards significantly improved students’ early reading skills. The mean score increased from 19.64 on the pretest to 36.36 on the posttest. The paired-sample t-test showed a statistically significant difference between students’ early reading skills before and after the intervention (p < 0.001), while the N-Gain score of 0.8441 was classified as high. In addition, classroom observation results indicated that 81.82% of the students were categorized as very active during the learning process. These findings suggest that the multisensory strategy assisted by picture word cards is effective in improving the early reading skills of first-grade elementary school students. Thus, multisensory strategies assisted by picture word cards can be used as an alternative learning to improve the initial reading ability of elementary school students.